Implementasi model pembelajaran Pendidikan Pancasila berbasis kesehatan mental untuk pencegahan bullying - Paiman Paiman; Joko Wahono; Ahmad Nasir Ari Bowo; Luqman Novianto; Oktavia Kurnia Wati (Curricula: Journal of Curriculum Development, 2026)
The implementation of Pancasila Education in schools has largely focused on theoretical instruction, with limited integration of mental health perspectives. As a result, teachers often have insufficient understanding of mental health concepts, while students experience various mental health challenges. This study aims to describe and develop an effective mental health–based model for implementing Pancasila Education to prevent bullying. Using an exploratory qualitative approach with a multiple-case study design, the research was conducted in six senior and vocational high schools in Yogyakarta. Data were collected through interviews, observations, and document analysis and were validated through triangulation of methods and data sources. Data analysis followed the interactive model of Miles and Huberman. The findings indicate that the implementation model comprises four key stages: establishing learning identity, identifying learning problems, formulating learning objectives, and implementing learning activities. Teachers function as facilitators who create safe and supportive learning environments, while students actively develop social and emotional awareness. This model positions schools as inclusive learning ecosystems that support character development and bullying prevention.